The method of overcoming the edge effect of the collection plate in the electrostatic spinning process: Auxiliary plate method. (2nd January 2018) - Ji-jie, Deng; Hong-chao, Dai; Min, Wang
ABSTRACT: During the electrostatic Spinning Process, the polymer solution forms a Taylor cone under the action of a high voltage electrostatic field, and then the electric field force overcomes the surface tension of the solution, and the non-Newtonian fluid viscous resistance, thus the jet is formed. The main reason for the instability of the jet in the space is that the jet is accompanied by the multi-field coupling of the electric field, the force field and the flow field at the same time in the course of movement. As the electrostatic induction makes the edge of the metal collection plate produce a tip effect, the instability of the jet whipping is aggravated, and the uniformity of nanofiber deposition and fiber quality is seriously affected. In this paper, a method of adding metal electrodes under the metal collection plate and loading the negative power source on the electrode is proposed. The finite element analysis software COMSOL Multiphysics 5.0 is used to establish the geometric model. The influence of the shape and distance of the metal plate on the edge effect of the collection plate was studied. It is found that the edge effect of the electric field distribution of the collection plate can be improved obviously when the metal cross is added at 2 cm below the collection plate and the negative power is applied.